2017
DOI: 10.3390/catal7020066
|View full text |Cite
|
Sign up to set email alerts
|

A Recyclable Fluorous Hydrazine‐1,2Bis(Carbothioate) Organocatalyst for the Synthesis of ꞵ‐Chloroethers with N‐Chlorosuccinimide

Abstract: Abstract:A novel fluorous hydrazine-1,2-bis(carbothioate) was prepared. It showed good catalytic activity in the synthesis of β-chloroethers with N-chlorosuccinimide under mild reaction conditions. This fluorous organocatalyst could be recovered and recycled several times with good purity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…It has since been shown that, by introducing Brønsted acid catalysts in NXS-mediated haloalkoxylation reactions, times could be reduced and the scope of the reactions increased, all while retaining Markovnikov selectivity. Such halogenation reactions have been demonstrated to be promoted by H 2 SO 4 , 172 NH 4 OAc, 173 thiourea 174 and a more elaborate recyclable polyfluorinated hydrazine 1,2-bis(carbothioate) organocatalyst 175 (Scheme 35). Typically, the Brønsted acidity of the additive is implicated in activation of the succinimide carbonyl oxygen, via a hydrogen bonding interaction, to promote electrophilic halogen formation.…”
Section: Alkene Difunctionalisationmentioning
confidence: 99%
“…It has since been shown that, by introducing Brønsted acid catalysts in NXS-mediated haloalkoxylation reactions, times could be reduced and the scope of the reactions increased, all while retaining Markovnikov selectivity. Such halogenation reactions have been demonstrated to be promoted by H 2 SO 4 , 172 NH 4 OAc, 173 thiourea 174 and a more elaborate recyclable polyfluorinated hydrazine 1,2-bis(carbothioate) organocatalyst 175 (Scheme 35). Typically, the Brønsted acidity of the additive is implicated in activation of the succinimide carbonyl oxygen, via a hydrogen bonding interaction, to promote electrophilic halogen formation.…”
Section: Alkene Difunctionalisationmentioning
confidence: 99%